(3TQM ebOeI GHf GdMGLH aj GdfMhs - (3eMeO Hf GdMSjf GdMSjfj GdGSJQGHGOj GdSeGcj, aNQ GdOjf,J (B715 (3g` s ((3GdMVQI GdebOSI GdZQhjI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LdJ GdGDI Yf Cf JMGW HbO hHYO abO WGdH Edi HYV ef GYJfi HUdGM MGdg hGSYag HeG JSYg ebOQJi ai ebJQMGJ CeGdg JYdjb eG jLQi eLQi GdTQM s
(3BNQgG (B:s
(3hdG Jdi gPg GdRjGOg gGA GdScJ HNdGa RjGOI GdGfcGQ dC, gPg EfeG JROG EPG de jbUO Gdhba hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3cJH CUdgG GdeUfa SfI (B682(3g`s
(3bGd GdSjhWi hgPG CYXe TQhMgGs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3eJaQbGJs